Laparoscopic Pyloromyotomy for Hypertrophied Pyloric Stenosis – Experience of 14 Class (Medical Forum Monthly, 2024)
Aim of study: To share the first ever national experience about laparoscopic pyloromyotomy and its technical details Study design: Descriptive study Place and Duration of Study: Study conducted at private hospital at Nawabshah Sind from sept 2009 to Dec 2010, Introduction: Hypertrophic pyloric stenosis is a common problem in pediatric surgery. Conventional management by the open extra mucosal pyloromyotomy has been the method of choice for many decades. Advanced, minimally invasive surgery also allows successful laparoscopic management of this entity. Material &methods: In this study 14 cases of laparoscopic pyloromyotomy, concentrating on technical details. Patients operated at some private hospital Nawabshah. Results: 14 patients underwent laparoscopic pyloromyotomy with standard technique. Initial operating time was more of initial learning curve . The infants tolerated the operative procedure well. There was one conversion to the open method because of immaturity of patient and technical difficulty. Conclusion: Our experience suggests that laparoscopic pyloromyotomy can be a safe and efficient procedure, but during the learning phase, laparoscopy should be decided on a case-by-case basis and performed by an experienced laparoscopic surgeon. Careful selection of patients is helpful to increase confidence and operative comfort.